Effects of a novel pesticide-particle conjugate on viability and reactive oxygen species generation in neuronal (PC12) cells. (April 2015) - Sooresh, Aishwarya; Sayes, Christie M.; Pine, Michelle
Abstract Development of new methods and compounds to eradicate insect vectors are desperately needed. To that end, our team has previously described the synthesis and characterization of a conjugate comprised of a silver nanoparticle core encapsulated by the pyrethroid pesticide, deltamethrin (pesticide encapsulated silver nanoparticle termed "PENS"). For this current work, the PENS conjugate was tested in neuronal cultured cells to compare the cytotoxic responses to the unconjugated pesticide deltamethrin – a known neurotoxic agent and pristine silver nanoparticles. The PC12 (pheochromocytoma of the rat adrenal medulla) cell line was chosen as a model neuronal culture system. Cells were exposed to known concentrations of PENS, deltamethrin or silver nanoparticle suspensions to assess the degree of toxicity in vitro. After 24 hours of incubation, cell viability and intracellular reactive oxygen species (ROS) were measured. Bright field images of high dose exposures to dosing solutions were also acquired to evaluate cell morphology. Exposure to PENS resulted in a 17% decline in viability at the highest concentration of 45 µM while exposure to deltamethrin caused a 47% decrease. These results suggest that cellular viability was less adversely affected by PENS than by the deltamethrin. Also, ROS production following PENS exposure indicated that the newly developed conjugate was responding in a similar manner as that of cells treated with deltamethrin only.